Analisis Pemanfaatan Serbuk Gergaji Kayu Dan Egg Tray Sebagai Bahan Alternaltif Peredam Suara Pada Genset - Gemanial, Juan; Napitupulu, Robert; Juanda, Juanda (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Noise is a serious problem that affects human health and comfort. This study aims to develop natural soundproofing materials from sawdust and egg trays as a more economical alternative to conventional soundproofing materials. Using an experimental method, this study analyzed the effect of volume fraction and specimen thickness on the sound absorption coefficient. The ANOVA results showed that both factors had a significant effect on certain frequencies. Specimens with a volume fraction of 40%:10% and a thickness of 20 mm produced the highest sound absorption coefficient of 0.163, while specimens with a volume fraction of 35%:15% and a thickness of 10 mm recorded the lowest value of 0.04. These findings indicate that the optimal combination of volume fraction and thickness can increase the effectiveness of the material in reducing noise, providing a sustainable solution to overcome noise problems in the surrounding environment.